Substitution Effect of Purple Sweet Potato Flour (Ipomea batatas) and Green Ocra (Abelmoschus esculentus) As a High Dietary Fiber Snack Bar for Obese Adolescent Girls - Ramadhani, Siti Nur; Mustafa, Annasari; Suwita, I Komang; Pudjirahaju, Astutik (Poltekkes Kemenkes Palu, 2024)
The trend of obesity among adolescent girls aged 10 – 19 years increased from 4.2% in 2014, 4.5% in 2015, and 4.7% in 2016. Followed by southeast asia in 2014 increased from 1.9% to 2.1% in 2015, and 2.3% in 2016. Riskesdas reported prevalence of obesity in adolescent girls was higher than adolescent boys, which was 1.5% in 2010, 1.9% in 2013, and 4.5 % in 2018. This study aims to analyze the effect of purple sweet potato and green ocra as a subtitutes for snack bars by considering chemical quality, nutritional quality, and organoleptic quality for obese adolescent girls. The study was carried out by using 4 levels of treatment with proportion wheat flour: purple sweet potato flour: green ocra that is P0 (100: 0: 0), P1 (20: 40: 40), P2 (20: 30: 50), and P3 (20: 20: 60). The results of the study showeded that purple sweet potato flour and green ocra had a significant effect (p<0.05) on water content, ash, protein, fat, carbohydrates, energy value, dietary fiber, color, taste, and texture but did not have a significant effect (p>0.05) on aroma snack bars. Furthermore, the best level treatment is P2 (20: 30: 50), with the highest panelist acceptance and high in dietary fiber that is 6,99 ± 0,035 g/100 g in which good for obese adolescent girls. Serving size of snack bar P2 (20: 30: 50) is 55 grams according to Recommended Dietary Allowance for adolescent girls aged 16 – 18 years and 10% of the daily requirement for snacks.